IMPLEMENTASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN PEMROGRAMAN KOMPUTER - Isroqmi, Asnurul (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
Implementation of character education in learning, especially in schools or higher education institutions can be done by exploring the values of learning itself. Education toward the formation of character to the learners is the responsibility of all educators. The guidance should be done by all subject teachers and all lecturers, not only charged to teachers or lecturers of certain subjects who do have a dominant portion in character education. One course that may be considered to have very little portion in character education learning is a course that studies programming languages or computer programming. However, when viewed from the objectives and learning process, then this course has many values or learning norms that can be developed as a character education education. This study aims to explore norms or values of characters contained in computer programming learning that can be implemented in everyday life. Some of the character values that can be implemented from computer programming learning include: problem-solving skills, systematic thinking, logical thinking, meticulous detail and creativity through project-based learning, cooperative and discussion methods.